2013
DOI: 10.18081/ajbm/2333-5106-013-12/38-48
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin reduces myocardial injury following global ischemia and reperfusion via suppression of myocardial inflammatory response

Abstract: Ghrelin is a small endogenous peptide principally produced and secreted by the gastric mucosa, with a major role in appetite and metabolism regulation. We hypothesized that antiinflammatory therapy, as produced by exogenous administration of ghrelin, would decrease the myocardial inflammatory response to global hypothermia I/R, thereby affording myocardial protection. Heterotopic cervical heart transplantation that allows to subject donor hearts to global hypothermic ischemia and blood reperfusion, which very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The half life of fructosamine level then will increase when there is reduction in protein turnover, so fructosamine is useful to measure the peripheral metabolic effect in those with thyroid diseases ( 19 ). Furthermore, it was found in our study that there is significant correlation between serum TSH and serum fructosamine and this finding also reported by Koga ( 20 ). The explanations for the abnormally high fructosamine levels in normoglycemic hypothyroid patients are:…”
Section: Discussionsupporting
confidence: 92%
“…The half life of fructosamine level then will increase when there is reduction in protein turnover, so fructosamine is useful to measure the peripheral metabolic effect in those with thyroid diseases ( 19 ). Furthermore, it was found in our study that there is significant correlation between serum TSH and serum fructosamine and this finding also reported by Koga ( 20 ). The explanations for the abnormally high fructosamine levels in normoglycemic hypothyroid patients are:…”
Section: Discussionsupporting
confidence: 92%
“…Many authors [10,11] believed that the regular use of some anti hyperlipidemic drugs improve hearing loss in hyperlipidemic patients with presbycusis so we excluded those patients from our study to avoid bias result due to above mentioned causes. No statistically significant difference was found between both groups in terms of age and the most affected age group was at seventh decade while the least one at ninth decade (table3.1),This result is similar to the study of Parmar et al [12] , while disagree with the findings [13,14] they found a significant relationship with age and mentioned that older age are associated with poorer auditory function and most affected age group was at sixth decade.…”
Section: Discussionsupporting
confidence: 68%
“…Differently, Klokkari and colleagues found that surgical treatment had a greater and significant improvement of symptoms and neurophysiological parameters at six months. While, at 3 and 12 months, the results were not significant in favor of surgery or conservative treatment (P>0.05) [11][12][13]. Differently also, at 20 weeks after randomization in Hui et al study, surgery had a significant greater symptomatic improvement than those with steroid injection (p<0.001) [14].…”
Section: Distribution Of Study Groups By Surgical Outcomementioning
confidence: 84%